Influence of Tricuspid Regurgitation After Heart Transplantation: A Single-center Experience. Issue 3 (17th February 2023) - Krey, Rebecca; Sommer, Wiebke; Meyer, Anna; Rivinius, Rasmus; Schlegel, Philipp; Frey, Norbert; Karck, Matthias; Warnecke, Gregor; Arif, Rawa
Abstract : Background: Tricuspid valve regurgitation (TVR) is often observed after orthotopic heart transplantation. However, there is a scarcity of data regarding long-term outcomes of patients with TVR. Methods: Between January 2008 and December 2015, 169 patients underwent orthotopic heart transplantation at our center and were included in this study. TVR trends and associated clinical parameters were retrospectively analyzed. TVR was assessed after 30 d, 1 y, 3 y, and 5 y, and groups were defined according to changes in TVR grade: constant (group 1; n = 100), improvement (group 2; n = 26), and deterioration (group 3; n = 43). Survival, outcome with regard to operative technique, and long-term kidney and liver function during follow-up were assessed. Results: Mean follow-up time was 7.67 ± 4.17 y (median 8.62, Q1 5.06, Q3 11.16). Overall mortality was 42.0%, with differences between the groups ( P < 0.01). Cox regression analysis revealed improvement of TVR as a significant predictor for survival (hazard ratio 0.23; 95% confidence interval, 0.08-0.63, P < 0.01). After 1 y 2.7%, after 3 y 3.7%, and after 5 y 3.9% of the patients showed persistent severe TVR. Creatinine levels after 30 d and 1, 3, and 5 y showed significant differences between the groups ( P = 0.02, P < 0.01, P < 0.01, and P = 0.01), deterioration of TVR being associated with higher creatinine levels during follow-up. Conclusions: Deterioration of TVR is associated with higher mortality and renal dysfunction. Improvement of TVR may function as a positive predictor for long-term survival after heart transplantation. Improvement of TVR should be a therapeutic goal offering a prognostic value for long-term survival.